Innovative Hard Isolation Techniques in GPON for Modern Power Distribution Networks - Jiangang Lu; Jiajia Fu; Xingnan Li; Yutu Liang (IEEE Access)
The transition of power distribution networks to digital and intelligent systems necessitates the integration of advanced communication technologies. Traditional communication methods, which often require separate networks for different services, lead to increased equipment, limited installation space, and higher consumption of optical fiber resources. Gigabit Passive Optical Network (GPON) technology, known for its high-speed broadband access, reliability, and scalability, presents a robust solution for real-time monitoring, control, and management of power distribution networks. However, GPON faces significant challenges in ensuring secure and effective isolation of different network segments, particularly in industrial scenarios where network performance and security are critical. This study aims to develop and evaluate innovative hard isolation techniques specifically designed for GPON in modern power distribution networks. By designing robust isolation mechanisms, implementing these techniques in a simulated GPON environment, and evaluating their performance under various scenarios, this research seeks to enhance security and operational efficiency. The results demonstrate that the proposed hard isolation techniques significantly improve the security and reliability of GPON systems, making them ideal for modern power distribution networks. This research provides practical insights and guidelines for implementing secure communication in power distribution networks, contributing significantly to the field and supporting the ongoing digital transformation of power grids.